Community bank activities as correlates of rural development in Ikwuano local government area, Abia state (2021)
This study investigated community bank activities as correlates of rural development in Ikwuano Local Government, Abia State, Nigeria. Thg study adopted a descriptive survey research design. Population for the study consisted of all adult indigenes resident in Ikwuano and the Community Banks Staff. Stratified random sampling technique was used in drawing out sample from the Population making a total of 107 respondents, that consisted of 90 indigenes and 17 staff of Community Bank. Structured questionnaire titled “Community Bank Activities and Rural Development” was used to obtain data which were analysed using simple Statistical tools of frequency counts and percentages for both demographic information and research questions. The findings of the study revealed that community banks’ activities were significantly related to rural development in Ikwuano LGA. The result showed that community banking has significant impacts on the development of rural economy in Ikwuano LGA. The study concluded that government and private organisations and members of communities have great roles to play in the development of rural economy in Order to meet up with urban economy. It was, therefore, recommended that government should make conscious effort to provide basic infrastructures in the rural areas to motivate micro finance institutions to operate without any hindrances; micro finance banks should be encouraged to lend to rural dwellers based on relationship to build their assets for improved livelihood in the rural economy